2019
DOI: 10.1084/jem.20190158
|View full text |Cite
|
Sign up to set email alerts
|

Primary prostate cancer educates bone stroma through exosomal pyruvate kinase M2 to promote bone metastasis

Abstract: Prostate cancer (PCa) metastasizes selectively to bone through unknown mechanisms. In the current study, we identified exosome-mediated transfer of pyruvate kinase M2 (PKM2) from PCa cells into bone marrow stromal cells (BMSCs) as a novel mechanism through which primary tumor-derived exosomes promote premetastatic niche formation. We found that PKM2 up-regulates BMSC CXCL12 production in a HIF-1α-dependent fashion, which subsequently enhances PCa seeding and growth in the bone marrow. Furthermore, serum-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 57 publications
3
126
0
Order By: Relevance
“…Furthermore, exosome size was measured using NTA, and the majority of vesicle particles were 50-150 nm in diameter. CD9 and CD63 are known exosomal protein markers routinely used for the determination of serum exosomes [25][26][27] . These results demonstrated that we have successfully extracted exosomes from serum.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, exosome size was measured using NTA, and the majority of vesicle particles were 50-150 nm in diameter. CD9 and CD63 are known exosomal protein markers routinely used for the determination of serum exosomes [25][26][27] . These results demonstrated that we have successfully extracted exosomes from serum.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the biological mechanisms underlying this hypothesis are not yet known in detail, most of the evidences obtained in the literature confirm that the treatments for ablative purpose of the primitive tumor, aiming to reduce the local load of disease, are able to positively influence the biological behavior of secondary locations and their response to adjuvant therapies 40 , resulting in an overall improvement of the OS, as well as quality of life. With particular regard to the radiometabolic treatment with 223Ra, it is known that this acts directly on the microenvironment surrounding the bone metastases 41 ; in our opinion it is reasonable to think that the mentioned microenvironment is, in a complex way, favored by the presence of the primary site of disease and that consequently its ablation would be decisive for a better control of systemic disease 42 .…”
Section: Role Of Primary Tumor Cytoreduction In Mcrpcmentioning
confidence: 99%
“…CXCL12 and RANKL, cytokines that are overexpressed by osteoblast-lineage cells and circulate in the blood, can attract CXCR4 and RANK, which are highly expressed on mammary tumor cells, inducing the latter to migrate to the bone surface. A new study regarding prostate cancer bone metastasis demonstrated that prostate cancer cells that produce exosomes can transfer pyruvate kinase M2 (PKM2) into bone marrow stromal cells and up-regulate CXCL12 in these cells (Dai et al, 2019). A similar mechanism remains to be elucidated for breast cancer bone metastasis.…”
Section: Bone Cellsmentioning
confidence: 99%